Mean individual biomass (mib) of ground beetles (coleoptera, carabidae) as indicator of succession processes in postindustrial areas - Renata Kędzior; Artur Szwalec; Paweł Mundała (Acta Scientiarum Polonorum. Formatio Circumiectus)
Carabid beetle mean individual biomass (MIB) was analysed in three postindustrial areas, where different environment regeneration types were observed. In total three postindustrial dumps were selected, two of them with spontaneous succession (age about 70 and 15–20 years) and one recultivated (age about 15–20 years). Moreover undisturbed forest was chosen as reference area. Additionally in research areas observations concerning changes in the abundance and dominance of individuals characteristic for open and forest habitats were done. During the field studies 1871 carabids were caught and indicated to species level. The results showed significant differences in MIB values according to regeneration type and succession age. Generally according to one-way Anova analysis MIB values increased with stand age, but there are also difference according to spontaneously revegetaed and recultivated areas. Comparing postindustrial areas with the same age, but with different type of regeneration (spontaneous or recultivation), the MIB values was lower in recultivated area. In these areas, the lowest number of carabids forest species was observed too, which may indicate a strongly disturbed and slow rate of assemblages regeneration. Our results indicate that the mean individual biomass index (MIB) can be usefull tool for assessment succession rate in strongly disturbed postindustrial areas.